Perceptions of academic staff and students of senior high school in implementing game-based exercises in physical education classes—a research protocol for a qualitative descriptive study - Donald Manlapaz; Jose Avelino Vergara; Keisha Marie Bea Alpuerto; Iszaac Khalil Señora De Los Santos; Michaela Urian Enriquez; Zamantha Zamora Manicio; Joshua Emmanuel Ferrera Mendres; Casey Gwyn Salvaleon Tolosa; Zachary Gabriel Dee Vilela; Zeraia Ezra Gabriel Alonzo Zabat (BMJ Open)
Background The COVID-19 pandemic has taken a toll on both physical activity and fitness as several pursuits and activities have been restricted. Coupled with this, increased food intake and sedentary lifestyles have produced poor physical health outcomes. Online physical education classes have been more difficult to conduct given the limitations of the setup. As such, exergaming has been identified as a possible educational tool that could improve students’ motivation, participation and fitness levels and reduce negative behaviours in class while contributing to the current curriculum.Objectives The study explores the perspectives of both the physical education academic staff and senior high school students from the University of Santo Tomas on the implementation of exergaming to determine the feasibility of exergaming as an educational tool in the Philippines’ physical education curriculum.Methodology A descriptive qualitative design will be used and participants will be selected through criterion sampling. The authors will conduct a process of question development and pilot FGDs beforehand to ensure smooth proceedings. Once done, they will undergo FGDs conducted through Google Meet. Data will be coded and analysed via thematic analysis using manual coding and NVivo V.12 software to summarise central themes and perceptions.Ethics and dissemination This study will abide by the Nuremberg Code, Declaration of Helsinki, Belmont Report, Data Privacy Act of 2012 and National Ethical Guidelines (for health-related research) of 2017. The study has received approval from the University of Santo Tomas (UST)-College of Rehabilitation Sciences (CRS) Ethics Review Committee. All participant data will be labelled according to random two-digit computer generated codes to preserve anonymity and stored in password-protected laptops and Google Drive folders to preserve confidentiality. Results will be made available to individual UST physical education academic staff and senior high school students prior to publication in peer-reviewed journal.